2016
DOI: 10.1080/00450618.2016.1153150
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the timing of anterior fontanelle closure in a Western Australian population

Abstract: Closure of the anterior fontanelle is generally accepted to occur within the first two years of life. However, statistical quantification of the precise timing of closure in a Western Australian population has not been explored. The current study examined MDCT scans of 68 individuals between birth and 3.91 years to assess the timing of anterior fontanelle closure. Using OsiriX, the scans are viewed in axial and multiplanar reconstructed (MPR) images and three-dimensional volume rendered reconstructions. Anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The only other CT‐based fontanelle study was Australian and analysed its data in 6‐monthly groups. The mean size of the Māori/Pasifika AF in 0–6 months was 580 mm 2 , smaller than the average of 693 mm 2 in the Australian study …”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The only other CT‐based fontanelle study was Australian and analysed its data in 6‐monthly groups. The mean size of the Māori/Pasifika AF in 0–6 months was 580 mm 2 , smaller than the average of 693 mm 2 in the Australian study …”
Section: Discussionmentioning
confidence: 86%
“…The mean size of the M aori/Pasifika AF in 0-6 months was 580 mm 2 , smaller than the average of 693 mm 2 in the Australian study. 10 To date, Perera et al have conducted the largest study of clinically assessed AF size in the neonate (n = 2215); this crosssectional study demonstrated the extent of the normal variation present in the Sri Lankan population, with 97% of neonates having a SA between 90 and 450 mm 2 . 20 Published literature has demonstrated significant ethnic variation in fontanelle size, with averages ranging from 225 mm 2 (AE79 mm 2 ) in the Hispanic population to 340 mm 2 (AE60 mm 2 ) in Nigeria.…”
Section: Closure Of the Afmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to racial differences, geographic location, and nutritional status (8,9,22). The mean size of AF in the first six months in the Maori/Pasifika group was 580 mm 2 (21) and with an average value of 693 mm 2 was in the Australian study (25). In our study, the median of the AF area was 605 ± 514.30 mm 2 which was higher than the Maori/Pasifika study and lower than the Australian study, which indicates the variation of AF among populations.…”
Section: Discussionmentioning
confidence: 96%